Roles of Bone Morphogenetic Protein Type I Receptors and Smad Proteins in Osteoblast and Chondroblast Differentiation - Fujii, Makiko (The American Society for Cell Biology, 1999)
The biological effects of type I serine/threonine kinase receptors and Smad proteins were examined using an adenovirus-based vector system. Constitutively active forms of bone morphogenetic protein (BMP) type I receptors (BMPR-IA and BMPR-IB; BMPR-I group) and those of activin receptor–like kinase (ALK)-1 and ALK-2 (ALK-1 group) induced alkaline phosphatase activity in C2C12 cells. Receptor-regulated Smads (R-Smads) that act in the BMP pathways, such as Smad1 and Smad5, also induced the alkaline phosphatase activity in C2C12 cells. BMP-6 dramatically enhanced alkaline phosphatase activity induced by Smad1 or Smad5, probably because of the nuclear translocation of R-Smads triggered by the ligand. Inhibitory Smads, i.e., Smad6 and Smad7, repressed the alkaline phosphatase activity induced by BMP-6 or the type I receptors. Chondrogenic differentiation of ATDC5 cells was induced by the receptors of the BMPR-I group but not by those of the ALK-1 group. However, kinase-inactive forms of the receptors of the ALK-1 and BMPR-I groups blocked chondrogenic differentiation. Although R-Smads failed to induce cartilage nodule formation, inhibitory Smads blocked it. Osteoblast differentiation induced by BMPs is thus mediated mainly via the Smad-signaling pathway, whereas chondrogenic differentiation may be transmitted by Smad-dependent and independent pathways.